EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN TIPE THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI POKOK HIMPUNAN DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Ikawati, Nur; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Journal of Mathematics and Mathematics Education, 2016)
Abstract: The aim of the research was to know the effect of learning models on mathematics learning achievement viewed from the student Adversity Quotient (AQ). The learning models compared were the cooperative learning model of the Group Investigation with scientific approach (GI-S), the cooperative learning model of the Think Pair Share with scientific approach (TPS-S), and model of classical learning with scientific approach (K-S). The type of the research was a quasi experimental research with the factorial design of 3 x 3. The population were all students of Junior High School in Bantul regency on academic year 2014/2015. The samples of  the research were taken by using the stratified cluster random sampling. The instruments used were mathematics achievement test and questionnaires of AQ. The hypotheses of the research were analyzed by using the two-way analysis of variance with unbalanced cells at the significance level of . The results of the research are as follows. 1) GI-S gives better mathematics achievements than TPS-S, and both gives better mathematics achievements than K-S. 2) Students with AQ type of climber have better mathematics achievements than students with AQ type of camper and type of quitter, while students with AQ type of camper have better mathematics achievements than students with AQ type of quitter. 3) For GI-S and TPS-S, students with AQ type of climber and type of camper have the same mathematics achievements, and students with AQ type of climber and type of camper gives better mathematics achievements than students with AQ type of quitter. For K-S, students with AQ type of climber have better mathematics achievements than students with AQ type of camper and type of quitter, and both have the same mathematics achievements. 4) For students with AQ type of climber and type of quitter, GI-S, TPS-S, and K-S gives the same mathematics achievement. For students with AQ type of camper, GI-S and TPS-S gives the same mathematics achievements, and both gives better mathematics achievements than K-S.Keywords: GI, TPS, Classical, Scientific Approach, AQ